Generalization of the Cramer Formula - Syavavko, M. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We apply the method of parametrized continued fractions to the solution of systems of linear algebraic equations on the basis of their Liouville–Neumann formal power series. We construct an analog of the Cramer formula, which is also applicable to the cases of singular, ill-posed, and rectangular matrices.